Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How would I solve these differential equations? Thanks so much for the help!

$$P'_0(t) = \alpha P_1(t) - \beta P_0(t)$$ $$P'_1(t) = \beta P_0(t) - \alpha P_1(t)$$

We also know $P_0(t)+P_1(t)=1$

share|cite|improve this question
up vote 4 down vote accepted

Note that from the equation you have $$P'_0(t) = \alpha P_1(t) - \beta P_0(t) = -P'_1(t)$$ which gives us $P'_0(t) + P'_1(t) = 0$ which gives us $P_0(t) + P_1(t) = c$. We are given that $c=1$. Use this now to eliminate one in terms of the other.

For instance, $P_1(t) = 1-P_0(t)$ and hence we get, $$P'_0(t) = \alpha (1-P_0(t)) - \beta P_0(t) \Rightarrow P'_0(t) = \alpha - (\alpha + \beta)P_0(t)$$

Let $Y_0(t) = e^{(\alpha + \beta)t}P_0(t) \Rightarrow Y'_0(t) = e^{(\alpha + \beta)t} \left[P'_0(t) + (\alpha + \beta) P_0(t) \right] = \alpha e^{(\alpha + \beta)t}$

Hence, $Y_0(t) = \frac{\alpha}{\alpha + \beta}e^{(\alpha + \beta)t} + k$ i.e. $$P_0(t) = \frac{\alpha}{\alpha + \beta} + k e^{-(\alpha+\beta)t}$$ $$P_1(t) = 1 - P_0(t) = \frac{\beta}{\alpha + \beta} - k e^{-(\alpha+\beta)t}$$

share|cite|improve this answer
Thank you so much! Much appreciated. – icobes Mar 19 '11 at 2:09
One question: I don't follow how you get a + ke^−(α+β)t term for P_0(t). Wasn't Y_0(t) a product? Thanks. – icobes Mar 19 '11 at 2:15

Use $P_0(t)+P_1(t)=1$ to turn it into $P_0'(t)=\alpha-(\alpha+\beta)P_0(t)$, which you should be able to solve.

share|cite|improve this answer
Could you give me a hint on how to solve P_0′(t)=(1−α−β)P_0(t)? I've never learned how to solve differential equations before and this was a question for a probability class so that is why I am completely lost. Thanks so much! – icobes Mar 19 '11 at 2:05
Note I corrected the algebra. You might look at for a start. – Ross Millikan Mar 19 '11 at 2:09

There is a general method to solve such equations, if we view them as a linear system of equation

$$y'(x) = A y(x)$$

When $A$ is a matrix with constants, the solution can be written in terms of the exponent matrix $e^{Ax}$.

More details can be found here.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.